(untitled) (Research, Society and Development, 2022)
The aim of this study was to evaluate the multiplication of S. aureus during whey powder production in laboratory scale. Whey was inoculated with 106 CFU∙ mL-1 of the S. aureus mixed culture at the beginning of the processing and the persistence of the microorganism after pasteurization, vacuum evaporation and drying was evaluated. The recontamination of whey by biofilms was also evaluated. Population of 102 CFU∙mL-1 of S. aureus was found after vacuum evaporation. The microorganism was able to multiply in concentrated whey during the crystallization of lactose, which infers that it is possible to form a biofilm during this stage. Confocal microscopy analysis confirmed the presence of adhered cells after 4 h of process (103 CFU∙cm2). After 12 h of incubation, the number of adhered cells was approximately 105 CFU∙cm2. Sessile cells of S. aureus in stainless steel were able to return to the planktonic phase. After spray drying, it was verified that the S. aureus population in the powder was 103 CFU∙g-1. The results obtained in laboratory scale points to the need of quality assurance systems to control the steps of industrial whey powder production.